2020
DOI: 10.1186/s12865-020-00367-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the response profile of deciduous pulp fibroblasts stimulated with E. coli LPS and E. faecalis LTA?

Abstract: Background Oral fibroblast immunological responses to bacterial stimuli are well known. However, there are few studies about pulp fibroblasts from deciduous teeth (HDPF) responses, which are important for the treatment of pulp infections in children. The aim of this study was to evaluate expression and production of inflammatory cytokines and chemokines by HDPF when challenged with bacterial antigens normally present in advanced caries lesions. Methods Triplicate HDPF from 4 children (n = 4; 2 boys and 2 girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…E. coli LPS stimulates the production of pro-inflammatory factors: CCL2, IL-8 and IL-6 [ 41 ]. Less intense upregulation occurs for IL-4, GCFS, GM-CSF and CCL5, as well as for IL-1β, IL-10, IL12p70, IL-17A, TNF-α, INF-λ [ 41 ] and TNFβ [ 42 ]. The maturation and release of IL-1β is stimulated by a combination of LPS and ATP.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli LPS stimulates the production of pro-inflammatory factors: CCL2, IL-8 and IL-6 [ 41 ]. Less intense upregulation occurs for IL-4, GCFS, GM-CSF and CCL5, as well as for IL-1β, IL-10, IL12p70, IL-17A, TNF-α, INF-λ [ 41 ] and TNFβ [ 42 ]. The maturation and release of IL-1β is stimulated by a combination of LPS and ATP.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they found a similar expression of the regulatory cytokine IL10 between healthy dental pulp tissue and dental pulp tissue exposed to moderate caries; the present study also reports no difference in IL-10. Similarly, Colombini-Ishikiriama et al (Colombini-Ishikiriama et al, 2020) and Keller et al (Keller et al, 2010) observed a differential expression of IL1b, IL6, IL8, and TNFa in cultures of pulp fibroblasts of deciduous teeth stimulated with Escherichia colilipopolysaccharide (EcLPS) or Enterococcus faecalislipoteichoic acid (EfLTA). However, they also detected a differential expression of IL10.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Colombini-Ishikiriama et al. ( Colombini-Ishikiriama et al., 2020 ) and Keller et al. ( Keller et al., 2010 ) observed a differential expression of IL1β, IL6, IL8, and TNFα in cultures of pulp fibroblasts of deciduous teeth stimulated with Escherichia coli -lipopolysaccharide (EcLPS) or Enterococcus faecalis -lipoteichoic acid (EfLTA).…”
Section: Discussionmentioning
confidence: 87%
“…Studies have confirmed that in cases of shallow caries, Gram‐positive bacteria account for a higher proportion, while in cases of deep caries and pulpitis, the proportion of Gram‐negative bacteria is higher [ 6 ]. Previous studies reported that both LTA and LPS were used as an inflammation model for dental pulp cells [ 7 , 8 , 9 , 10 ]. Our previous studies compared dental pulp cell inflammation models constructed using LTA and LPS, and the different treatment times with LTA and LPS (1, 2, 3, 5 and 7 days) [ 5 ].…”
mentioning
confidence: 99%